Bank Guarantee as A Third Party in The Event of Default at PT. BNI (Persero), Tbk Market Branch Office Mayestik Jakarta - Yulia Mujiaty; Darma Wijaya; Deasy Novayanti; Siti Nurjanah; Prihatiningsih Prihatiningsih (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Bank Guarantee as Third Party Guarantee in the Event of Default at PT. BNI (Persero), Tbk Pasar Mayestik Branch Office, Jakarta Bank guarantee, is a payment guarantee given by the bank to a party in the form of a document. Default occurs when the obligation is not carried out or is negligent in the agreement between the creditor and the debtor. PT Bank State of Indonesia (Persero), Tbk. was founded as the central bank in Indonesia with the name "Bank Negara Indonesia" on July 5, 1946. On October 30, 1946, Bank Negara Indonesia was upgraded to Persero and given the name PT Bank Negara Indonesia, according to Law Number 17 of 1968. Collecting data in preparation is observation, interview, and literature study methods with qualitative descriptive analysis. PT. BNI (Persero), Tbk Pasar Mayestik Jakarta Branch Office carries out Bank issuance The guarantee has three stages, namely the filing stage, screening stage, and releaser stage. When applying for a bank guarantee, customers are required to attach underlying documents such as preparing funds in a savings account and a letter of principle approval from insurance.